On optimal tax differences between heterogeneous groups - Klaus Beckmann; Nele E. Franz; Andrea Schneider (Helmut-Schmidt-Universität - Universität der Bundeswehr Hamburg, Fächergruppe Volkswirtschaftslehre, 2014)
This paper considers optimal linear tax structures that are differentiated according to group membership. Groups can be heterogeneous with respect to both preferences and abilities. Contrary to most arguments in favour of tax privileges for certain groups, e.g. gender-based taxation, it is shown that consideration of the first moment of the relevant distributions (the average labour supply elasticity of the groups) is insufficient. We discuss the factors on which efficient differentiation would depend.
Keywords: H21; D31; 330; optimal linear income taxation; preference heterogeneity; genderbased taxation; horizontal equity